Iceberg discharge events in the northwest Pacific and related sequence of Kamchatka glaciations over the last 190 kyr. (15th February 2022) - Gorbarenko, Sergey A.; Shi, Xuefa; Liu, Yanguang; Vasilenko, Yuriy P.; Yanchenko, Elena A.; Derkachev, Aleksandr N.; Bosin, Aleksandr A.; Velivetskaya, Tatyana A.; Malakhova, Galina Yu.; Zou, Jianjun; Kirichenko, Ivan S.; Artemova, Antonina V.; et al.
Abstract: Evidence of meltwater and ice rafted debris from the Tenji and Detroit seamounts in the northwestern corner of the North Pacific are key to understanding ice sheet dynamics across the Kamchatka Region. Marine isotopic stages 6.5–1 were established in this study for the Tenji Seamount sediment core based on accelerator mass spectrometry (AMS) 14 C data, benthic foraminifera δ 18 O stratigraphy, and relative paleointensity excursions. Records of planktic foraminifera δ 18 O and ice rafted debris (IRD) in sediment cores pertaining to the last 190 kyr were used to outline several periods of surface water freshening and increased accumulation of coarse terrigenous grains induced by iceberg supply and melting in the northwest Pacific. Iceberg discharge events (IDEs) were reconstructed over the last and penultimate glacial periods in the central and eastern parts of the Okhotsk Sea and southwestern part of the Bering Sea using relevant published proxies. Similar reconstructions of IDEs were also performed for two published sediment cores from the Detroit Seamount. Synthesis of planktic foraminifera δ 18 O and IRD records along with other related proxies from the studied areas concordantly revealed five IDEs in the northwest Pacific and its marginal seas during the last 190 kyr: IDE 1 (42–29 ka), IDE 2 (76–57 ka), IDE 3 (118–110 ka), IDE 4 (152–141 ka), and IDE 5 (179–160 ka). Data showed that IDEs 4–1 occurred at low values of Earth obliquity and under a weak Aleutian Low, facilitating snowfall precipitation and enhancing glacier formation at Kamchatka, which is a priority area for capturing atmospheric moisture transferred into northeast Asia. Compared with the other IDEs, IDEs 2 and 5 were more pronounced and prolonged events over the last 190 kyr. In addition, IDE 2 was also characterised by a catastrophic and short IRD peak that was probably forced by the influx of lake water from the Central Kamchatka Depression. It is likely that IDEs 2 and 1 occurred during phases I (more extensive) and II (less extensive) of the published Kamchatka glaciations during the Late Pleistocene. Highlights: Planktic δ 18 O and ice rafted debris as tools for iceberg discharge in the NW Pacific. Dated records of iceberg evidences in sediments of NW Pacific and marginal Seas. Five dated iceberg discharge events (IDE) in NW Pacific inferred by data synthesis. Five periods of Kamchatka glaciations related with NW Pacific IDEs over last 190 ka.